ChemInform Abstract: Synthesis of Diazonaphthoquinones from Naphthols by Diazo‐Transfer Reaction. Issue 45 (November 2015) - Kitamura, Mitsuru; Sakata, Rie; Tashiro, Norifumi; Ikegami, Azusa; Okauchi, Tatsuo
Abstract using 2‐azido‐1, 3‐dimethylimidazolium chloride